Problem of psycho-correction of social estrangement and disadaptation of the ATO participants - Демченко, Я. А. (Київський національний університет імені Тараса Шевченка, 2017)
The article considers and analyzes the features of social exclusion and maladaptation in servicemen who returned from the zone of combat operations, and suggested approaches to its psychological correction. It is proved that the use of psycho-technologies to overcome the above-mentioned phenomena contributes to the recognition of the professional role positions of the subjects, the strengthening of ethnic identity, ideological and political identity, the perception of oneself as a member of a particular social group or groups; strengthening of interpersonal relations with close surroundings; awareness and acceptance of professional qualifications, competencies and achievements; reduction of violations of social identity.

У статті розглянуто і проаналізовано особливості соціальної відчуженості та дезадаптації у військовослужбовців, які повернулися із зони бойових дій, та запропоновано підходи до її психологічної корекції. Доведено, що використання психотехнологій подолання означених феноменів сприяє усвідомленню професійно-рольових позицій суб’єктів, посиленню етнічної ідентичності, світоглядної та політичної ідентичності, сприйняття себе членом певної соціальної групи або груп; укріпленню міжособистісних взаємин з близьким оточенням; усвідомленню та прийняттю професійної приналежності, компетентності, досягнень; зменшенню порушень соціальної ідентичності.
Проблема психокорекції соціальної відчуженості та дезадаптації учасників АТО
Keywords: psychocorrection; social estrangement; disadaptation; the ATO participants; психокорекція; соціальна відчуженість; дезадаптація; учасники АТО